2017
DOI: 10.1111/ppl.12591
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of plant hormone levels in rice shoots grown under microgravity conditions in space: its relationship to maintenance of shoot growth

Abstract: We investigated the effects of microgravity environment on growth and plant hormone levels in dark-grown rice shoots cultivated in artificial 1 g and microgravity conditions on the International Space Station (ISS). Growth of microgravity-grown shoots was comparable to that of 1 g-grown shoots. Endogenous levels of indole-3-acetic acid (IAA) in shoots remained constant, while those of abscisic acid (ABA), jasmonic acid (JA), cytokinins (CKs) and gibberellins (GAs) decreased during the cultivation period under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…Whereas expression of Os08g0167000 (MR = 13.711), which encodes one of the half-size adenosine triphosphate-binding cassette transporter subgroup G (ABCG), was induced by salicid acid and repressed by auxin treatment [ 198 ]. Finally, Os05g0447200 is AUX2 , one of the auxin-responsive genes, and was highly induced under microgravity conditions [ 199 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas expression of Os08g0167000 (MR = 13.711), which encodes one of the half-size adenosine triphosphate-binding cassette transporter subgroup G (ABCG), was induced by salicid acid and repressed by auxin treatment [ 198 ]. Finally, Os05g0447200 is AUX2 , one of the auxin-responsive genes, and was highly induced under microgravity conditions [ 199 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to gravity-associated membrane alteration, we think several microgravity induced physiological changes may also be beneficial to frozen protection: 1) Concentrations of soluble sugars, glucose, sucrose and total starch were substantially increased in Space shuttle flight sweetpotato stem 54 , and soluble sugars enhanced in tobacco callus cells under rotation simulated microgravity 55 ; 2) In space, microgravity environment had no obvious effect to rice shoots auxins, but reduced the expression of ACC synthase, the key enzyme of ethylene biosynthesis 3 , and ethylene is a negative regulator of cold resistance; 3) Numerous experiments indicated that calcium in cells increased under real or simulated conditions 5,56 ; 4) Genes expression changed under real microgravity in space and simulated ground experiments. Functions of "major space genes" include Ca 2+ and lipid signaling, cell membrane biosynthesis, total metabolism, carbohydrates and lipid response to stress, auxin-signaling, and heat shock protein (HSP) thought to support the organization of cytoskeleton in adaptive response to microgravity [57][58][59][60] .…”
Section: Resultsmentioning
confidence: 99%
“…Over the past 20 years, our understanding of the impact of microgravity on organism physiology has increased. Plant-based life regeneration ecosystems have helped scientists to study plant growth in a ground-controlled environment by simulating short duration of altered-gravity, and the improved design of plant growth chambers in the International Space Station (ISS) has allowed researchers to study the mechanisms of life adaptation to approximate zerogravity condition [2][3][4][5][6] . Because plants could be an essential integral part of longterm bioregenerative life support system 2 , plant culture in space remains a high priority strategy for all space exploration plans.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain normal root gravitropism, plants must receive and respond to the gravity signal appropriately [37]. We investigated the effects of a microgravity environment on the root growth and endogenous hormone IAA in 12–2.…”
Section: Resultsmentioning
confidence: 99%